Bridging knowledge to commercialization: the good, the bad, and the challenging - Baycan, Tüzin; Stough, Roger R. (Springer Science and Business Media LLC, 2012)
This paper investigates a new emerging phenomenon in the debate of knowledge-based economic growth called “bridging knowledge to commercialization”. The paper considers commercialization of knowledge as a complex and a multi-faceted phenomenon and aims to highlight “the good”, “the bad” and “the challenging” in commercialization of knowledge from a taxonomic perspective. The paper has four objectives: (1) to examine the emerging concepts in bridging knowledge to commercialization while addressing related issues in the literature and to offer a conceptual framework on the basis of a typology of metaphores for knowledge; (2) to highlight the societal benefits of commercialization of knowledge in a regional development context; (3) to underline the value conflicts and differences in culture and perspectives in the valuation of knowledge in order to better understand the commercialization process; and (4) to highlight the challenges for academia, industry and government while describing the critical framework conditions that are needed to effectively foster commercialization of knowledge. While addressing the academic, societal, spatial, cultural and ethical implications of knowledge commercialization, the paper highlights retrospects and prospects from regional development perspective.